Measuring the efficiency of the Algerian banking sector during the period 2006-2017: Applying DEA - Bettioui, nesrine; ali dahmane, Mohammed (Journal of Research in Finance and Accounting, 2022)
This study seeks to attempt to measure the efficiency of the Algerian banking sector during the period from 2006 to 2017 using Data Envelopment Analysis (DEA) method through its two basic models, the constant volume yield model (CCR) and the variable volume yield model (BCC). Based on a sample of nine commercial banks (public and private). Accordingly, the study concluded with the following most important results : Commercial banks in Algeria public and private achieved low levels of efficiency during the study period according to model, Public banks have also achieved optimum levels of complete technical efficiency (PTE) compared to private banks, and this is due to the excessive control of the state in the work of this sector, which was positively reflected on their efficiency. Therefore, we conclude in general that there is no competition in the field of Algerian banking activity and the existence of a quasi-monopoly on the part of national public banks. Therefore, the state must continue the reform process in the banking sector to improve its efficiency.